Populism and Health Policy in Latin America; Comment on "A Scoping Review of Populist Radical Right Parties' Influence on Welfare Policy and its Implications for Population Health in Europe" - Mary A. Clark; Amy Patterson (Kerman University of Medical Sciences, 2021)
This commentary focuses on Latin America, a region known for its rich variety of populist politicians and some of the most extensive welfare states in the Global South. Contemporary Latin America offers examples of left-wing and right-wing populist leaders, none of whom demonstrate the same focus on excluding immigrants from welfare state benefits as that noted by Chiari Rinaldi and Marleen Bekker in the European context. We see this contrast not because immigrants' access to health services is less important in Latin America, but because Latin American populists are more focused on internal "enemies." The commentary concludes with observations regarding Latin American populist leaders' handling of the Coronavirus disease 2019 (COVID-19) pandemic.